Transmission of the Sustainable Development Strategy as a Global Agenda to the EU, National and Local Level - Petrović, Vesna; Mirović, Ivan (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2021)
Sustainable development as a modern concept implies economic development harmonized with the social, economic and environmental component. The main focus of sustainable development strategies is finding a balance between economic and social growth with care for nature protection, and the encouragement of ecological production with the aim of preventing the degradation of natural resources and limiting climate change. The most prominent global endeavor dealing with this paradigm is the Agenda 2030 for sustainable development proclaimed by the UN in 2015 defined 17 sustainable development goals in order to enhance globalization, its positive effects and elimination or reduction of their harmful consequences. The objective of this paper is to elaborate and review this multilateral agenda, its strategic documents and analyze its transmission to various lower levels in terms of institutional, strategic planning and operational dimensions. The authors will present the main strategic documents and actions prepared and undertaken by the institutions of the European Union in order to follow this Agenda. We also aim to elaborate on national and local initiatives aimed at incorporating the sustainable development concept in their developmental strategies and action plans.